2021
DOI: 10.1016/j.pnpbp.2021.110292
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress and sleep problems in healthcare workers in a developing context during COVID-19 pandemic: Implications for workplace wellbeing

Abstract: Background Emotional wellbeing of healthcare workers is critical to the quality of patient care, and effective function of health services. The corona virus disease-2019 (COVID-19) pandemic exerted unique physical and emotional demands on healthcare workers, however little is known about the emotional wellbeing of healthcare workers during the COVID-19 pandemic in resource-restricted settings. This study investigated the prevalence of psychological distress, and sleep problems in healthcare worker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 26 publications
5
29
0
Order By: Relevance
“…We believe this is the first large-scale use of GHQ-12 to assess the mental health status among dental healthcare workers in China. The positive rate of the mental health status of GHQ-12 was 23.8%, which was close to the healthcare workers in Nigeria (23.4%) ( 48 ), lower than the Chinese neurologists (37.8%) ( 25 ), healthcare workers in Japan (65.6%) ( 49 ), doctors in emergency medicine, anesthesia and intensive care medicine in the UK and Ireland (44.2%) ( 50 ) and obstetrics healthcare providers in Italy (51.1%) ( 51 ). It illustrated that the positive rate of mental health status of dental healthcare workers was relatively low, which could be attributed to the effective containment of COVID-19.…”
Section: Discussionsupporting
confidence: 52%
“…We believe this is the first large-scale use of GHQ-12 to assess the mental health status among dental healthcare workers in China. The positive rate of the mental health status of GHQ-12 was 23.8%, which was close to the healthcare workers in Nigeria (23.4%) ( 48 ), lower than the Chinese neurologists (37.8%) ( 25 ), healthcare workers in Japan (65.6%) ( 49 ), doctors in emergency medicine, anesthesia and intensive care medicine in the UK and Ireland (44.2%) ( 50 ) and obstetrics healthcare providers in Italy (51.1%) ( 51 ). It illustrated that the positive rate of mental health status of dental healthcare workers was relatively low, which could be attributed to the effective containment of COVID-19.…”
Section: Discussionsupporting
confidence: 52%
“…Stress has been shown to be one of the main factors contributing to HCW insomnia. The change in normal daily routine, economic uncertainty, and concerns about contracting the COVID-19 have all contributed to increased HCW insomnia [ 11 , 12 ]. According to studies during the COVID-19 pandemic, HCWs serving on the front-line experience more sleep disorders and poorer sleep quality as compared with non-HCWs [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…77 In addition, general negative emotions caused by the pandemic are associated with complaints of daytime functioning and affective symptoms. 10,78,79 However, Rasskazova 80 pointed out that complaints of daytime functioning difficulties depended not so much on the level and content of anxiety but on the level of dysfunction that interferes with everyday activities during the period of COVID-19. Therefore, while applying the PSQI to the frontline COVID-19 medical population, the deletion or modification of the "daytime dysfunction" subscale may be considered.…”
Section: Discussionmentioning
confidence: 99%
“…1 Several other Chinese studies found that compared with non-frontline or nonmedical staff, the prevalence of sleep disorders in frontline COVID-19 medical staff is higher (16.4%-61.6%), with the epidemic of anxiety and depression. [2][3][4][5][6] Similarly, multiple investigations in Egypt, Turkey, Iran, and other Middle East regions [7][8][9] ; Nigeria; Serbia; other African regions 10,11 ; and Brazil 12 revealed that the proportion of poor sleep in medical staff fighting COVID-19 was greater than 45.7%, and the presence of anxiety features (P < .001) as well as depressive features (P < .001) could be used as significant independent predictors of poor sleep quality. 13 These studies suggest a high incidence of poor sleep in frontline COVID-19 health care workers.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation